2019
DOI: 10.3390/f10030237
|View full text |Cite
|
Sign up to set email alerts
|

Drought Impacts and Compounding Mortality on Forest Trees in the Southern Sierra Nevada

Abstract: The increase in compounding disturbances, such as “hotter droughts” coupled with insect outbreaks, has significant impacts on the integrity of forested ecosystems and their subsequent management for important ecosystem services and multiple-use objectives. In the Southern Sierra Nevada, years of severe drought have resulted in unprecedented tree mortality across this mountainous landscape. Additionally, past land management practices, including fire suppression, have led to overly stocked, homogenous forest st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 39 publications
2
17
0
1
Order By: Relevance
“…Notably, a similar pattern was shown by Stovall et al 65 in a study confined to the southern Sierra Nevada (i.e., the hottest, driest portion of the more spatially extensive results we present here) with a strong positive tree height/mortality relationship in areas with the greatest vapor pressure deficit and no tree height/mortality relationship in areas with the lowest vapor pressure deficit. Our work suggests that the WPB was cueing into different aspects of forest structure across an environmental gradient in a spatial context in a parallel manner to the temporal context noted by Stovall et al 65 and Pile et al 70 , who observed that mortality was increasingly driven by larger trees as the hot drought proceeded and became more severe. A temporal signal of bark beetles attacking larger and larger host trees reflects the positive feedback between forest structure and bark beetle population dynamics as the population phase cycles from endemic to epidemic 13 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Notably, a similar pattern was shown by Stovall et al 65 in a study confined to the southern Sierra Nevada (i.e., the hottest, driest portion of the more spatially extensive results we present here) with a strong positive tree height/mortality relationship in areas with the greatest vapor pressure deficit and no tree height/mortality relationship in areas with the lowest vapor pressure deficit. Our work suggests that the WPB was cueing into different aspects of forest structure across an environmental gradient in a spatial context in a parallel manner to the temporal context noted by Stovall et al 65 and Pile et al 70 , who observed that mortality was increasingly driven by larger trees as the hot drought proceeded and became more severe. A temporal signal of bark beetles attacking larger and larger host trees reflects the positive feedback between forest structure and bark beetle population dynamics as the population phase cycles from endemic to epidemic 13 .…”
Section: Discussionsupporting
confidence: 78%
“…The positive main effect of host tree mean size on ponderosa mortality rates tracks the conventional wisdom on the dynamics of WPB in the Sierra Nevada, as well as other primary bark beetles 18 . WPB exhibits a preference for trees 50.8-76.2 cm DBH 68,69 , and a positive relationship between host tree size and levels of tree mortality attributed to WPB was reported by Fettig et al 14 in the coincident field plots as well as in other recent studies 9,15,70 . Larger trees are more nutritious and are therefore ideal targets if local bark beetle density is high enough to successfully initiate mass attack and overwhelm tree defenses, as can occur when many trees are under water stress 7,13,24 .…”
Section: Discussionmentioning
confidence: 56%
“…(2018) found that increased evaporation rates due to warmer temperatures (1°C warmer than the previous decade) intensified the drought impact on mountain hydrology, reducing the fractional allocation of precipitation to runoff by 30%. These rising temperatures also amplified drought‐induced stress on watershed ecology as tree mortality across drought‐stricken landscapes was recorded at multiple studies (Goulden et al., 2019; Guardiola‐Claramonte et al., 2011; Pile et al., 2019; Young et al., 2017). This is noteworthy, since increasing temperatures also increase plant water demand while soil moisture decreases due to reduced precipitation levels.…”
Section: Discussionmentioning
confidence: 97%
“…We assessed mortality rates for some wellstudied tree species and many other tree species that, to our knowledge, do not have any published mortality rates. The most common focal conifer species in recent mortality work have been conifers in the genera Abies, Pinus, and Juniperus (Gaylord et al 2013, Krofcheck et al 2014, Mortenson et al 2015, Fettig et al 2019, Flake and Weisberg 2019, Pile et al 2019, McDowell et al 2019. We improve on previous (Table 3 v www.esajournals.org mortality research for these species by including populations over wide areas, as well as including species closely related to common focal species that are less well studied.…”
Section: Factors Most Important To Recent and Future Forest Mortalitymentioning
confidence: 99%